Resilience in Human Resource Management: Organizational Adaptation Strategies in the Tourism Industry during Times of Uncertainty and Crisis - Retno Widowati; Damdam Damiyana (Brilliant International Journal Of Management And Tourism, 2025)
Organizational resilience has become a strategic necessity in increasingly volatile and uncertain environments. This study examines how strategic human resource management (HRM) practices specifically HR flexibility, leadership agility, and strategic workforce planning contribute to enhancing organizational resilience. The research problem lies in the fragmented understanding of how these HR components interact and under what conditions they effectively foster resilience. To address this, the study aims to develop a conceptual model integrating these three HRM dimensions, with employee engagement as a mediating variable and organizational culture as a moderating factor. A qualitative exploratory approach was applied through a structured literature review of 35 peer reviewed articles published between 2020 and 2024. Thematic content analysis was conducted using NVivo software to identify patterns and relationships among the variables. The findings reveal that HR flexibility supports operational adaptability, leadership agility enhances strategic responsiveness, and workforce planning ensures long term preparedness. Employee engagement amplifies the effectiveness of these HR strategies, while organizational culture determines the extent to which they translate into resilience outcomes. This integrative framework highlights the importance of aligning HR practices within a supportive cultural context. The study concludes that organizational resilience emerges not from isolated HR initiatives but from their synergistic interaction within a dynamic capability framework. These findings offer both theoretical contributions and practical implications for HR leaders seeking to strengthen resilience through human capital strategies.